An indirect treatment comparison of the efficacy of semaglutide 1.0 mg versus dulaglutide 3.0 and 4.5 mg. Issue 11 (9th August 2021) - Pratley, Richard E.; Catarig, Andrei‐Mircea; Lingvay, Ildiko; Viljoen, Adie; Paine, Abby; Lawson, Jack; Chubb, Barrie; Gorst‐Rasmussen, Anders; Miresashvili, Nino
Abstract: Aim: To compare the effects of semaglutide 1.0 mg versus dulaglutide 3.0 and 4.5 mg on HbA1c and body weight in patients with type 2 diabetes. Materials and Methods: A Bucher indirect comparison was conducted to compare efficacy outcomes of semaglutide 1.0 mg versus dulaglutide 3.0 and 4.5 mg using published results from the SUSTAIN 7 and AWARD‐11 trials. Sensitivity analyses using individual patient data from SUSTAIN 7 and aggregate data from AWARD‐11 were conducted to explore the impact of adjustment for cross‐trial imbalances in baseline characteristics. Results: Semaglutide 1.0 mg significantly reduced HbA1c versus dulaglutide 3.0 mg, with an estimated treatment difference (ETD) of −0.24%‐points (95% confidence interval [CI] −0.43, −0.05), with comparable reductions in HbA1c versus dulaglutide 4.5 mg with an ETD of −0.07%‐points (95% CI −0.26, 0.12). Semaglutide 1.0 mg significantly reduced body weight versus dulaglutide 3.0 and 4.5 mg with an ETD of −2.65 kg (95% CI −3.57, −1.73) and −1.95 kg (95% CI −2.87, −1.03), respectively. Sensitivity analyses supported the primary analysis findings. Conclusions: This indirect comparison showed significantly greater reductions in HbA1c with semaglutide 1.0 mg versus dulaglutide 3.0 mg and comparable HbA1c reductions versus dulaglutide 4.5 mg. Semaglutide 1.0 mg significantly reduced body weight versus both dulaglutide 3.0 and 4.5 mg. With several glucagon‐like peptide‐1 receptor agonists available, information regarding their comparative efficacy can be valuable to clinicians.